Virtual art applications in promoting local entrepreneurial products on Shopee Malaysia - Naseri, Roszi Naszariah Nasni; Muthusamy, Geetha; Yahya, Wan Kalthom; Hasbullah, Nornajihah Nadia; Norizan, Nor Sabrena (Faculty of Art and Design, 2025)
Virtual art has emerged as a transformative force in the evolving landscape of digital retail, particularly within e-commerce platforms such as Shopee Malaysia. This review critically examines the role of virtual art encompassing digital illustrations, augmented visuals, motion graphics, and immersive design elements in promoting products by local entrepreneurs. It highlights how these creative tools enhance brand storytelling, strengthen consumer trust, and foster emotional engagement, especially for micro and small enterprises (MSEs) operating with limited marketing resources. Drawing upon interdisciplinary literature, the paper explores the ways in which Malaysian sellers utilize virtual aesthetics to embed cultural identity and product value in highly competitive digital marketplaces. In addition, it addresses the challenges faced by entrepreneurs, including limited design literacy, financial constraints, and low awareness of the strategic potential of visual content. The review concludes by identifying future opportunities for capacity building, platform support, and collaborative innovation to democratize the use of virtual art in local entrepreneurship.